The manifestations of legend through popular proverbs in the Algerian eastern region: a mythological study - Aggoune, Hanane; Djedid, Salah (Journal of Human Sciences, 2023)
Myths occupy a large place in the Algerian popular heritage, both tangible and intangible, as we find the legend that manifests itself in images, drawings and engravings on the rocks and walls of houses and temples, as we find examples of pottery and porcelain utensils, and we also find them on traditional clothing and carpets and furniture ... etc., and this has been established We searched for images of the presence of myths and the way in which they are used by the inhabitants of eastern Algeria, and we are looking for the indications that these myths carry, and the values which inculcate them, taking the popular example as a field of study and research because of its daily presence and its dominance of Algerian popular forms of expression.